Perspectives on patients and carers in leading teaching roles in interprofessional education. Issue 2 (4th March 2019) - Anderson, Elizabeth S.; Ford, Jenny; Thorpe, Lucy
ABSTRACT: The involvement of patients and carers is central to the values of interprofessional education (IPE) which aims to improve the experience of care and care delivery. Partnership arrangements with service users and carers within Higher Education Institutions face the same barriers relating to status, power, and resources, as the implementation of IPE. The complexity of these alignments can be explained by Activity Theory (AT). Using a qualitative research methodology we set out to consider the stakeholder perspectives on whether patients should progress from telling their stories to taking on a leading teaching role, within a well-established IPE workshop. Following the principles of Participatory Action Research, data were collected cyclically, using consultation meetings, interviews (with tutors and patients) and focus groups (with students). The work was overseen by a steering group who reviewed and clarified the analysis, informed by AT. All stakeholders endorsed the validity of patients as teachers. Two new leadership roles were proposed; patients as Co-Tutors and as Mentors supporting the workshop. Service users and carers were realistic about the support required for progression. Students were more ambivalent, recognizing the right of patients to tell their stories but having concerns about their competence and potential bias when in leading roles. There is overall support for the development of a progressive route for patients to move beyond telling stories into leading teaching roles in IPE, but this brings added complexity and requires a supportive infrastructure, careful preparation of students and further research.